PENGARUH MODEL PEMBELAJARAN ESTAFET WRITING TERHADAP KEMAMPUAN MENULIS CERPEN SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD NEGERI 22 JEPPE'E KECAMATAN TANETE RIATTANG BARAT KABUPATEN BONE - Abd Kadir A; Muhammad Ikhsan Sukaria; Dea Nurhadsyah (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This research is a quantitative research type of experimental research with a quasi-experimental design in the from of a Nonequivelent Control Group Design. The study aimed to determine whether there was a significant effect of the use of the Estafet Writing learning model on students’ short story writing skills in Indonesia language subjects for fourth-grade students of SD Negeri 22 Jeppe’e Tanete Riattang Barat, District Bone Regency. The variables in this study werw the Estafet Writing learning model as the independent variable and students’ short story writing skills as the dependent variable. The population in this study is all fourth-grade students of SD Negeri 22 Jeppe’e Tanete Riattang Barat District, probabilitBone Regency, totalling 30 students. This study uses a non-y sampling technique or saturated sample. The data collection technique used was a performance test in the from of short story writing. The data analysis techniques for this study are descriptive statistical analysis and inferential statictical analysis. The result of study show that descriptively, the average posttest of the experimental class was 78.20, while the average posttest score of the control class was 57.07. Based on inferential analysis using the Independent Samples t-Test, the results indicated a significant difference in shory story writing skills between the experimental class (Class A) and the control class (Class b) in Indonesia language subjects at SD Negeri 22 Jeppe’e, Tanete Riattang Barat District, Bone Regency. Therefore, it can be concluded that the use of the Estafet Writing learning model had a significant effect on students’ short story writing skills in Indonesia language subjects for fourt-grade students of SD Negeri 22 Jeppe’e Tanete Riattang Barat District, Bone Regency. Keywords: Estafet Writing Model, Short Story Writing Skills